1995
DOI: 10.1128/jb.177.22.6477-6485.1995
|View full text |Cite
|
Sign up to set email alerts
|

BvgAS is sufficient for activation of the Bordetella pertussis ptx locus in Escherichia coli

Abstract: BvgA and BvgS, which regulate virulence gene expression in Bordetella pertussis, are members of the two-component signal transduction family. The effects of growth conditions on the ability of BvgAS to activate transcription of fhaB (encoding filamentous hemagglutinin) and ptxA (encoding the S1 subunit of pertussis toxin) were assessed in Escherichia coli by using chromosomal fhaB-lacZYA and ptxA-lacZYA fusions. Although it had previously been reported that a ptxA-lacZYA transcriptional fusion was not activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 58 publications
3
26
0
Order By: Relevance
“…By the introduction of the respective loci into these mutants, several of these suppressor mutations could be mapped to either the bvg or the rpoA locus. Recent results obtained demonstrated that the BvgA transcription factor is able to interact directly with all virulence promoters analyzed so far, the ptx, cyaA, fha, and bvg loci (5,31,38,42). The localization of suppressor mutations within the bvg and rpoA loci is in agreement with these results and further strengthens the hypothesis that BvgA and the RNA polymerase ␣ subunit may interact physically during the transcription initiation process at the toxin promoters (7).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…By the introduction of the respective loci into these mutants, several of these suppressor mutations could be mapped to either the bvg or the rpoA locus. Recent results obtained demonstrated that the BvgA transcription factor is able to interact directly with all virulence promoters analyzed so far, the ptx, cyaA, fha, and bvg loci (5,31,38,42). The localization of suppressor mutations within the bvg and rpoA loci is in agreement with these results and further strengthens the hypothesis that BvgA and the RNA polymerase ␣ subunit may interact physically during the transcription initiation process at the toxin promoters (7).…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, these mutations in the bvg locus lead to avirulent bacteria, the so-called phase variants (23). Despite the coordinate regulation mediated by this two-component system, differential regulatory phenomena such as different induction kinetics of transcription of the various factors or different expression patterns in the heterologous host Escherichia coli were noted, which led to the classification of the virulence factors into two groups, (i) the two toxins PTX and CyaA and (ii) the other factors (33,34,42). These differences in their expression are also reflected by differences in the promoter structures of the two groups.…”
mentioning
confidence: 99%
“…The fact that RBH was capable of expressing all of the same phenotypic phases as RB50, however, indicates that BvgAϳP levels can be adjusted precisely and maintained indefinitely at specific levels in response to specific environmental cues, even when BvgA is maintained at a high level. Since there is considerable evidence that phosphorylation and dephosphorylation of BvgA are controlled only by BvgS (41,(45)(46)(47)(48), these data provide strong evidence that the kinase and/or phosphatase activity of BvgS can be adjusted to and maintained at intermediate levels. Our data also suggest that it is the absolute amount of BvgAϳP, rather than the ratio of BvgAϳP to BvgA, that is important in controlling gene expression, because this ratio must be well below one in RBH cells grown under Bvg iphase conditions but one or nearly one in RBL cells grown under Bvg ϩ -phase conditions and in RB50 cells immediately after a shift from Bvg Ϫ -phase conditions to Bvg ϩ -phase conditions, yet in all of these cases, the Bvg i phase is expressed.…”
Section: Discussionmentioning
confidence: 77%
“…Mechanistically, this could be due to a lower binding affinity of BvgA at ptx or to the need for higher-order multimers of BvgA. A recent study demonstrates that under certain growth conditions, BvgAS is in fact sufficient for modulation-responsive activation of the ptx locus in E. coli cells (39). Uhl and Miller suggest that the relevant difference between the growth conditions promoting ptx expression and conditions previously used is a slower rate of growth with a concomitant increase in BvgA levels.…”
mentioning
confidence: 99%